Aplicação e análise da utilização do software Eberick em um projeto residencial popular - Mariano, Mayara Aparecida da Cunha [UNESP] (2015)
Due to new technologies in civil engineering and the competition of the market, the demand for computer programs for the elaboration of structural projects of reinforced concrete is raising in a quick and efficient manner. This paper presents a study based on Eberick, a structural calculation software, and this software was applied to a low cost residence project. By performing structural calculation manually, it is possible to compare and analyze the criteria that Eberick uses for the design and detailing of structural elements like columns, beams and slabs. As the software functionality becomes clear, the engineer will use it careful and safely, exploring all of its resources and advantages